Immunosuppressive treatment for peripheral neuropathies in Sjogren's syndrome - a systematic review - Humă Andreea Camelia; Kecskeş Evelyn Maria; Tulbă Delia; Bălănescu Paul; Băicuş Cristian (Sciendo, 2020)
Background. Sjogren's syndrome (SS) is among the most frequent autoimmune diseases and one of its most severe extraglandular manifestations is peripheral neuropathy. There is no consensus about peripheral neuropathy treatment in SS. Our aim is to identify studies proving the efficiency of immunosuppressive treatment on peripheral neuropathies in SS.